Istitha’ah Dalam Haji (Studi Tematik Tafsir Ahkam Surah Ali Imran ayat. 97) - Syaikhu Syaikhu (Institut Agama Islam Negeri Palangka Raya, 2020)
ABSTRACTHajj is a form of worship that influences the personality of a Muslim. Therefore, the hajj was not just an ordinary trip, or just a sightseeing trip. The hajj became a very special